Diagnostic performance of 14-3-3η and anti-carbamylated protein antibodies in Rheumatoid Arthritis in Han population of Northern China - Zhang, Yuan; Liang, Yongming; Feng, Limei; Cui, Liyan (Clinica chimica acta, 2020)
•Single and multiple indicators can be combined together for identification of RA.•Positive of any two markers or only anti-CCP tend to be diagnosed as RA.•Four indicators were significantly positively correlated with each other. As we already know, Rheumatoid arthritis (RA) cannot be excluded when the rheumatoid factor (RF) or anti-cyclic citrullinated peptide antibody (anti-CCP) is negative. Here, we determined the application value of 14-3-3η protein, anti-carbamylated proteins antibodies (anti-CarP), as well as their potential role to diagnose RA together with RF or anti-CCP. Serum levels of anti-CCP, RF, 14-3-3η and anti-CarP antibodies were detected in 291 RA patients, 223 patients with autoimmune diseases except RA, and 156 healthy subjects recruited from Han population of Northern China. We examined the differences in the levels of these indicators among groups and compared the correlations between any two of the indicators. At the same time, a total of 12 testing strategies were established for comparison to maximize the diagnostic value. The levels of RF, anti-CCP, anti-CarP and 14-3-3η were significantly higher in RA patients (12.5;[9.36–15.7], 30.7;[25.7–35.6], 1.90;[1.70–2.01], 15.8;[10.8–20.8], respectively) compared with either interference-control group (1.24;[1.07–1.41], 0.64;[0.42–0.86], 0.51;[0.46–0.57], 0.33;[0.23–0.44], respectively) (p < 0.0001) or healthy-control group (1.03;[0.99–1.08], 0.49;[0.38–0.59], 0.28;[0.21–0.35], 0.55;[0.27–0.85], respectively) (p < 0.0001). Among all 12 detection strategies, the YI and κ value of a novel strategy that either double-positive of any 2 markers or single-positive of anti-CCP can be diagnosed as RA had the highest diagnostic value. The results of our study demonstrated that in Han population of Northern China, anti-CarP antibodies and 14-3-3η protein can be treated as valuable indicators of RA, especially when combined with RF and anti-CCP, the detection value is maximized.